Clinical deep remission and related factors in a large cohort of patients with rheumatoid arthritis - Liu, Jia-Jia; Li, Ru; Gan, Yu-Zhou; Zhang, Rui-Jun; Li, Jing; Cai, Yue-Ming; Zhao, Jin-Xia; Liao, Hua; Xu, Jing; Shi, Lian-Jie; Li, Ji; Li, Sheng-Guang; et al. (Chinese medical journal, 2019)
Clinical remission is the treatment target in rheumatoid arthritis (RA). This study aimed to investigate clinical remission and related factors in a large cohort of patients with RA. This study composed of 342 patients with RA. Data were collected by face-to-face interview of 1049 patients with RA who visited the Department of Rheumatology of three teaching hospitals from September 2015 to May 2016. The patients with RA were clinically assessed by rheumatologists and a four-page questionnaire was completed on site. Subsequently, patients fulfilled remission criteria were further analyzed. The practicability of different definitions of remission of RA was rated by a panel of rheumatologists. Sustained intensive disease modifying anti-rheumatic drug (DMARD) treatment was defined as a combination treatment with two or more DMARDs for at least 6 months. In this cohort of 342 patients with RA, the proportions of patients achieving remission were 38.0%, 29.5%, 24.9%, 21.1%, 19.0%, 18.1%, and 17.0%, based on criteria of disease activity score in 28 joints (DAS28) using CRP (DAS28-CRP), DAS28 using ESR (DAS28-ESR), routine assessment of patient index data 3 (RAPID-3), Boolean, simplified disease activity index (SDAI), clinical disease activity index, and the newly described clinical deep remission (CliDR), respectively. Boolean and CliDR are the best in practicability scored by rheumatologists (7.5 and 8.0, respectively). Compared with the non-sustained intensive group, sustained intensive treatment with DMARDs yielded higher remission rates of 25.6%, 23.8%, and 21.3% in patients with RA based on Boolean (χ = 3.937, P = 0.047), SDAI (χ = 4.666, P = 0.031), and CliDR criteria (χ = 4.297, P = 0.038). The most commonly prescribed conventional synthesized DMARDs (csDMARDs) in patients with RA was leflunomide, followed by methotrexate, and hydroxychloroquine. Compared with the non-remission group, patients achieving remission had a longer median duration of DMARDs (45.0 [22.8-72.3] months, Z = -2.295, P = 0.022). The findings in this study indicated that clinical deep remission is achievable in patients with RA. Sustained intensive DMARD treatment is needed to achieve a better outcome in RA.